Lipoteichoic acid of Enterococcus faecalis inhibits osteoclastogenesis via transcription factor RBP-J. Issue 1 (January 2019) - Wang, Shuai; Chin Heng, Boon; Qiu, Shuqi; Deng, Jing; Shun Pan Cheung, Gary; Jin, Lijian; Zhao, Baohong; Zhang, Chengfei
Lipoteichoic acid (LTA) of Enterococcus faecalis is a potent stimulator of inflammatory responses, but the effects of E. faecalis LTA on osteoclastogenesis remains far from well understood. This study showed that E. faecalis LTA significantly inhibited osteoclastogenesis of wild type murine bone marrow-derived macrophages (BMMs) in the presence of a high dose of RANKL, while the inhibition of osteoclastogenesis by E. faecalis LTA was significantly removed in BMMs with deficient expression of the transcription factor RBP-J. In addition, a few small osteoclasts were generated in BMMs with only E. faecalis LTA stimulation, presumably due to the production of TNF-α and IL-6. Furthermore, both p38 and ERK1/2 MAPK signaling pathways were activated after 24 h of E. faecalis LTA treatment, but these signaling pathways were not activated after 6 d of treatment with RANKL in mature osteoclasts. In conclusion, E. faecalis LTA, which induces inflammatory response, could inhibit RANKL-induced osteoclastogenesis via RBP-J in BMMs.